Keratinized Gingiva Determines a Homeostatic Behavior of Gingival Sulcus through Transudation of Gingival Crevice Fluid - Maria Luiza P. Lagos; Adriana Campos Passanezi Sant'Ana; Sebastião Luiz Aguiar Greghi; Euloir Passanezi (Hindawi Limited, 2011)
Objective. To shed light on the role of KG, its influence on periodontal behavior was investigated. Methods. Tissue fluid transudation was assessed in alveolar mucosa (P1A), outer gingival margin (P1B), at entrance of (P2) and within gingival sulcus (P3), before and after chewing of fibrous food in 16 patients portraying ≥2 mm KG at one tooth (group 1), and <2 mm at another homologous tooth (group 2). Results. There was a significant increase in GCF after chewing at P1B and P3 in group 1 and at P1A in group 2 (t-test, 𝑃<0.05). Conclusions. The results suggest that KG plays a role in marginal periodontal homeostasis.